Fuzzy Obstacle Avoidance for the Mobile System of Service Robots. (8th December 2020) - Tseng, Shih-Pang; Chen, Che-Wen; Kuan, Ta-Wen; Hsu, Yao-Tsung; Wang, Jhing-Fa
Abstract : This study implements Fuzzy logic-based obstacle avoidance and human tracking on an omnidirectional mobile system for service robots. The mobile system could be separated and combined with the robot which can be controlled remotely and switched to go forward and avoid obstacles in an indoor environment automatically. The system is able to track and go to the user according to the user's position. The omnidirectional wheel was adapted in the power system to perform translating and spinning movements. The translating movement enables the robot to avoid obstacles faster and flexibly in paths. With the spinning movement, the robot can quickly find the direction of the object. Finally, the experiments show that the proposed system has good performance in service environments.